Elementary School Teachers' Knowledge of Science, Technology, Engineering, and Mathematics (STEM) Based on Teacher Status - I Putu Anggi Pradnyasih; Putu Nanci Riastini; Komang Sujendra Diputra (Jurnal Ilmiah Sekolah Dasar, 2025)
The limited understanding of the Science, Technology, Engineering, and Mathematics (STEM) approach among elementary school teachers poses a challenge in creating innovative and meaningful learning. This study aims to describe elementary school teachers’ knowledge of STEM and the factors influencing it based on teacher status. The research employed a quantitative descriptive approach with a sample of 60 teachers, consisting of 30 guru penggerak and 30 guru non-penggerak, selected using multistage sampling and stratified random sampling techniques. Data were collected through knowledge tests and questionnaires and analyzed using descriptive statistics. The results show that elementary school teachers’ knowledge of STEM in Buleleng District is at a moderate level, with average scores of 58% for guru penggerak and 44% for guru non-penggerak, while the main factors influencing their knowledge are learning motivation (78%), personal experience (71.5%), and level of education (68.4%). The study concludes that efforts to enhance teachers’ STEM capacity need to be carried out evenly, regardless of teacher status. The implication is that schools and policymakers should provide continuous training, adequate facilities, and learning support to strengthen elementary school teachers’ STEM competencies.